Learning PHP Data Objects : a beginner's guide to PHP Data Objects, Database Connection Abstraction Library for PHP 5. /: a beginner's guide to PHP Data Objects, Database Connection Abstraction Library for PHP 5. (2007) - Unknown
No abstract available